Smart guide to sports medicine - Sobell, Sheila (John Wiley & Sons, 1999)
Smart Advice on the most common sports injuries-their diagnoses, treatments, and repercussions. Smart Ways to recover from surgery and exercise after an injury or illness-including alternative medicine.